Institutionalizing internal goods through Catholic school identity - Hurst, Christopher (Journal of Religious Education, 2024)
Catholic schools, in order to be Catholic, lay claim to a particular sense of what these schools are and what they are not; that is, they claim Catholic school identity. Organizations such as Catholic schools have a strong identity if these claims are central to their core mission, distinct from the claims of other organizations, and consistent over time. The distinctiveness of Catholic school identity implies that Catholic educational practice must be rooted in a particularly Catholic tradition, and the centrality of Catholic school identity implies that excellent Catholic schools can derive internal goods only available to these schools. But claims to a distinct identity are undercut by the pursuit of external goods such as wealth, power, and prestige, as these external goods are neither central to the mission of any school, nor do they distinguish Catholic schools from other forms of school. In particular, Catholic school principals must balance their schools’ need for legitimacy with their desire to claim a strong Catholic identity. This paper provides a framework for understanding the internal goods that comprise Catholic school identity, the external goods these schools need to survive, and the process of judgment principals must use to maintain Catholic school identity.